2020
DOI: 10.15244/pjoes/118384
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal Content in Soils Adjacent to the DK16-Route in Olsztyn (North-Eastern Poland)

Abstract: The paper discusses the problem of the impact of the road on the content of heavy metals in soil and the impact of land use on limiting the migration of these xenobiotics. The area submitted to the research stretched along Sielska Street in Olsztyn, which is a section of the DK 16 route connecting Olsztyn and Ostróda. This area varies in terms of land relief, land use and plant cover. Soil samples were taken on both sides of the street at a distance of 1, 10 and 20 m from the road. The content of trace element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Soils with such a heavy-metal content can be used for agricultural production without restrictions [ 81 ]. Other studies also confirmed that the content of heavy metals in the soils of the eastern region of Poland was relatively low and did not exceed the relevant standards [ 82 , 83 ].…”
Section: Resultsmentioning
confidence: 65%
“…Soils with such a heavy-metal content can be used for agricultural production without restrictions [ 81 ]. Other studies also confirmed that the content of heavy metals in the soils of the eastern region of Poland was relatively low and did not exceed the relevant standards [ 82 , 83 ].…”
Section: Resultsmentioning
confidence: 65%
“…According to national standards [44], the first two doses of each metal are the permissible content for arable land soils, and the third dose is the level proving soil contamination with these elements. Tests performed in areas exposed to continuous emission of pollutants often show an increased content of Pb, Cd and Zn in soils [5,9].…”
Section: Experiments Descriptionmentioning
confidence: 99%
“…This negative impact of trace elements is compounded by their continuous emissions into the natural environment from many anthropogenic sources [3][4][5][6]. In many areas exposed to intense anthropogenic activity, there is an increased content in heavy metals such as Cd, Pb and Zn [7][8][9]. Contamination of soil with Cd, Pb and Zn poses high threats to soil quality [7].…”
Section: Introductionmentioning
confidence: 99%
“…Dangerous factors of anthropogenic origin are involved in processes that intensify the migration of metals to the edaphotope, which contributes to the reduction of vegetation (devegetation) and water depletion (dehumidification) and is destructive to the agrophysical, physicochemical and biological properties of soils, providing them with toxic properties [1][2][3]. These transformations arise mainly from the deposition of heavy metals caused by the emissions of metal-bearing dust, liquid and solid industrial and municipal waste, agricultural fertilizers and plant protection products, and motor traffic flow through roads and streets [4][5][6][7][8][9][10][11][12]. Any metal (metalloid) can be considered an impurity if it is present where it is not desired or in a form or concentration that causes harmful effects to humans or the environment [13].…”
Section: Introductionmentioning
confidence: 99%